The Impacts and Economic Analysis of Jack Mackerel Meal Inclusion in Low Fish Meal Diets on the Growth and Feed Availability of Juvenile Rockfish (Sebastes schlegeli) - Yu Jin Sim; June Kim; Sung Hwoan Cho (Animals)
A two-way {dietary substitution source [chicken by-product meal (CBM), meat meal (MM), and tuna by-product meal (TBM)] × substitution level (25% and 50%)} ANOVA experimental design was adopted. The control (Con) diet included 55% FM. In the Con diet, 25% and 50% of FM were substituted with CBM, MM, and TBM, with the inclusion of 22% JMM exhibiting strong attractiveness for rockfish, named CBM25J, CBM50J, MM25J, MM50J, TBM25J, and TBM50J diets, respectively. All experimental diets were assigned to triplicate groups of fish. A total of 525 juvenile fish were distributed into 21 flow-through tanks. The CBM- and TBM-substituted diets achieved greater weight gain and specific growth rates (SGRs) of rockfish than the MM-substituted diets. Moreover, dietary 25% FM substitutions achieved greater weight gain and SGRs of rockfish than dietary 50% FM substitutions. Weight gain and SGRs of rockfish fed the Con, CBM25J, and TBM25J diets were superior to those of rockfish fed the CBM50J, MM50J, and TBM50J diets. Dietary 25% FM substitutions exhibited higher rockfish feed consumption than dietary 50% FM substitutions. None of the proximate compositions, amino and fatty acid profiles, or blood chemistry of the fish were significantly different among dietary treatments. The highest EPI was observed in the CBM25J diet. Conclusively, a 25% FM substitution with CBM, MM, and TBM with the inclusion of 22% JMM in the 55% FM-based diet could be made without reducing the growth and feed consumption of rockfish. Finally, the CBM25J diet produced the highest weight gain and SGRs of rockfish, as well as the highest economic return to farmers.